ON A METHOD FOR FINDING THE NUMERICAL SOLUTION OF CAUCHY PROBLEM FOR 2D BURGERS EQUATION - Rasulov, Mahir; Boran, Emine (European Scientific Journal, ESJ, 2015)
In this paper a new method is proposed for finding the numerical solution of the Cauchy problem for 2D Burgers equation with initial function consisting of four piecewise constants in a class of discontinuous functions. For this goal, a special auxiliary problem which has some advantages over the main problem is introduced. Using these advantages of the auxiliary problem, the numerical solution of the main problem is obtained. Some computer experiments are carried out.